Rhabdomyolysis-Induced AKI in Trauma Patients: Predictors of Dialysis Requirement in the Emergency Department, Khyber Teaching Hospital, Peshawar, Pakistan - Aman, Babar; Raza, Ali; Zulfiqar, Warda; Sohail, Muhammad Waheed; Khan, Fayaz (Indus Journal of Bioscience Research, 2025)
Background: Rhabdomyolysis-induced acute kidney injury (AKI) is a serious complication in trauma patients, often requiring dialysis if not promptly recognized and managed. Identifying predictors early in the emergency department (ED) setting is vital for optimizing outcomes. Aim: This study aims to determine the predictors of dialysis requirement in trauma patients presenting with rhabdomyolysis-induced AKI. Methods: A prospective observational study was conducted at the Emergency Department of Khyber Teaching Hospital, Peshawar, between January 2024 and March 2025. Adult trauma patients with serum creatine kinase (CK) levels >5000 U/L and rising creatinine were enrolled. Exclusion criteria included pre-existing CKD and non-trauma-related rhabdomyolysis. Clinical, biochemical, and radiological parameters were evaluated to assess the need for dialysis during hospitalization. Results: Among 300 patients with rhabdomyolysis-induced AKI, 80 (26.7%) required dialysis. Dialysis was more common in patients with elevated CK levels (>15,000 U/L: 76%), hyperkalemia (K⁺ >6.0: 68%), severe acidosis (pH <7.2: 65%), and oliguria (72%). Patients who received fluids after more than 2 hours had a 60% dialysis rate. In contrast, early interventions significantly reduced dialysis need: only 28% required dialysis with early fluid resuscitation, 35% with bicarbonate therapy, and 20% with a combined approach. Supportive care alone was associated with the highest dialysis rate (65%). Conclusion: Key predictors of dialysis in rhabdomyolysis-induced AKI include hyperkalemia, severe metabolic acidosis, and high serum CK levels. Early identification and aggressive management in the ED can prevent progression to dialysis.